Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1097/01.hs9.0000967436.08196.70
|View full text |Cite
|
Sign up to set email alerts
|

S131: A Randomised Assessment of the Sequential Addition of the Kinase Inhibitor Quizartinib to Intensive Chemotherapy in Older Acute Myeloid Leukaemia (Aml) Patients: Results From the Ncri Aml18 Trial

Abstract: The benefit of adding tyrosine kinase (TK) inhibition to intensive chemotherapy (IC) has not been demonstrated in patients aged >60yrs with newly diagnosed AML. Quizartinib (Quiz) is a class III receptor TKI with potent activity against FLT3 and clinical activity in relapsed/refractory FLT3-ITD+ AML. We have previously demonstrated that Quiz can be safely given sequentially after IC in older AML patients (Burnett et al, Blood 2013; 122:622).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The trial showed a significant improvement in median OS for patients receiving quizartinib compared to placebo (31.9 vs. 15.1 months, p = 0.032). Neither the Quantum FIRST trial nor the NCRI AML 18 trial [56] demonstrated a survival benefit to intensive induction chemotherapy with the addition of quizartinib in patients > 60 years with FLT3-mutated AML (Figure 1). The high TRM observed during the first 3 months of treatment is likely to have offset a survival benefit from quizartinib, with a 17.4% TRM rate in elderly patients [57].…”
Section: Recent Advancesmentioning
confidence: 99%
“…The trial showed a significant improvement in median OS for patients receiving quizartinib compared to placebo (31.9 vs. 15.1 months, p = 0.032). Neither the Quantum FIRST trial nor the NCRI AML 18 trial [56] demonstrated a survival benefit to intensive induction chemotherapy with the addition of quizartinib in patients > 60 years with FLT3-mutated AML (Figure 1). The high TRM observed during the first 3 months of treatment is likely to have offset a survival benefit from quizartinib, with a 17.4% TRM rate in elderly patients [57].…”
Section: Recent Advancesmentioning
confidence: 99%